Biological explorations : - Gunstream, Stanley E. (Pearson/Benjamin Cummings, 2009)
The level of rigor, user-friendly language, and abundant illustrations make this manual ideal for students who have had little, if any, prior science laboratory experience. Orientation, The Microscope,